Immediate results of combined and multivisceral resections for rectal cancer - S. G. Afanasyev; A. Yu. Dobrodeev; I. B. Khadagaev; S. A. Fursov; E. A. Usynin; А. S. Tarasova; D. A. Sorokin; V. V. Faltin; A. V. Usova (Сибирский онкологический журнал)
Background. Currently, the indications for multivisceral pelvic resections have increased dramatically. However, short-and long-term outcomes after these resections for locally advanced rectal cancer remain a subject of debate.The purpose of the study was to evaluate short-term surgical and oncological outcomes after multivisceral pelvic resections in patients with locally advanced rectal cancer.Material and methods. We analyzed surgical outcomes in 32 patients (13 men and 19 women) aged 44-69 years, with locally advanced rectal cancer, who were treated between 2010 and 2016. Of the 32 patients, 28 (87.5 %) had rectal cancer with invasion into adjacent organs (posterior wall of the bladder - 13, uterus - 10, ureters - 5, prostate - 4, vagina - 3; simultaneous damage to more than 2 organs - 14, multiple primary malignant tumors: rectal cancer + bladder cancer - 2, rectal cancer + endometrial cancer - 1, rectal cancer + rectal GIST - 1.Results. Total pelvic evisceration was performed in 6 (18.8 %) cases, combined resection of the rectum and adjacent organs was performed in 26 (81.2 %). Urinary tract resection was performed in 24 (75.0 %) patients. Of these patients, 13 (40.6 %) had primary plasty of the bladder and/or ureters. Postoperative surgical complications were observed in 11 (34.4 %) patients, of whom 7 (21.8 %) patients needed re-surgery. In 1 patient (3.1 %), who died in the early postoperative period, the cause of death was thrombosis of the right iliac vessels with subsequent acute renal failure. For patients with locally advanced rectal cancer, long-term outcomes were as follows: the overall and recurrence-free 2-year survival rates were 75 % and 56.3 %, respectively. All patients with multiple primary malignant tumors were alive with no evidence of disease recurrence at a follow-up of >24 months.Conclusion. Multivisceral resection in patients with locally advanced rectal cancer is a complex surgical procedure requiring the multidisciplinary team of surgeons. Despite high operative morbidity, proper perioperative management of the patients helps to achieve satisfactory immediate treatment outcomes. Long-term outcomes allowed us to consider such resections as a method of choice for locally advanced and multiple primary rectal cancers.